Níveis de julgamento de alunos de 1., 2. e 3. graus de ensino - Gasparin, Pedro (1979)
The judgment leveIs of' the students' of' the 1 st , 2 nd and Jrd grade of' the Private School System and of' the .University Foundation of' the town of' Lages - Santa Cata- --7ina -, is both a theoretical study and a study of' prac- ---tical rese8;rch which intends to check and discuss the re 1ations between the quality or the matur1.ty of' judgment and·the variable~ age, schooling leveI, intellectual abi ~ity, and socio-economic leveI of' the students under in- . -vestigation. The sample was aleatorily assorted among alI the stuãents f'rom the 8 th series, 1 st grade; the 2 nd ser1es, 2 nd d . d th Jrd . Jrd d' t 1 . gra e; an e. ser1es, gra e, 1n a ra ec 0- se to 20% f'rom the total population. Theref'ore, the sam- pIe consists of' 152 people. The specif'ic objectives which guided the study sum up in the analysis and discussion oi' the relationsb~ tween the. judgment leve~ and the other variables, _that ~s to say, age, schooling leveI, intellectual ability ~nd socio-economic leveI of'the students in questiono ~he results show: f'irst, that the absolute majE rity of' the people either f'rom the 1 st and 2 nd or f'rom the Jrd grade did not reach themore mature judgment le- -ve1s, that is to say: imaginative-explicativR and imagi~ native-explicative-understanding judgments; second, the students show a great dif'f'iculty in reasoning and judg- ment concerning the test of' logical. structure; third,the -variables age, schooling leveI, and socio-economic leveI generally relate positively to each other with the judg- ment level, although, concerning this research, the re- 1ation mentioned above seems to be weak •. That is probmly due to the little dispersion or great homogeneity of' the ·scores obtained by the studen~s. The homogeneity of' . re-- sul.ts casts f'orth some problems that mi€!>'ht be discussed ~n later studies which would indicate the conditions of .. ·,-development of the judgment process, ei ther interior or ·.,.exterior to the school. ·Some questions are delineated here, concerning ~~pecially the action of the school, the textbooks employ ->ed in it, the precarious conditions of the teachers, the -- ~rAditional conception of education. At the end of the present work, some researches are prop~sedt specially those which intend to improvethe - knowledge about the development of the judgment process, .as well as those which try to relate the teacher's soci2 , economic level with th~ students performance.